2019
DOI: 10.2478/rjdnmd-2019-0021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pancreatic and Extra Pancreatic Effects of Branched Amino Acids

Abstract: Background and aims: Leucine, Isoleucine, and Valine collectively known as Branchedchain amino acids (BCAAs), can be closely associated with metabolic dysregulates and with insulin resistance. We aimed to explore the role of BCAAs as potential treatment option for diabetes. Material and method: Bioassay the effect of BCAAs on MIN6 cell line on insulin secretion and pancreatic beta cells expansion, then were checked for inhibitory potential of pancreatic amylase, glucosidase and lipase as alternative approach f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In order to assess cell viability, treated cells were incubated at 37°C for 72 h. Negative control wells contained only fresh media. 14 Control wells were cells with DMSO. Then, 20 μL of 3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) was added to every well.…”
Section: Cell Viability Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess cell viability, treated cells were incubated at 37°C for 72 h. Negative control wells contained only fresh media. 14 Control wells were cells with DMSO. Then, 20 μL of 3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) was added to every well.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…IC50 values were detected as the average of three replicates (Graph pad prism, version 5.02 statistical programes was used). 14,15 Determination of apoptosis by flow cytometry Approximately 5×10 5 cells were cultured in 25 cm 2 flask. ten flasks of T47D cells were prepared, 16 one flask was used as a control (untreated cells) and three flasks were treated with IC50, IC75 and IC25 of ethanol extract of O. dayi and incubated for 72 h. Another three flasks were treated with IC50, IC75 and IC25 of ethanol extract of O. dayi and incubated for 48 h. The last three flasks were also treated with IC50, IC75 and IC25 of ethanol extract of O. dayi and incubated for 24 h. Then the number of cells were counted using hemocytometer according to the following formula: (Number of cell = average number of cells × 2 ×10000 × volume of cell suspension).…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…The Folin and Ciocalteu method 24 ; was used for the estimation of the total tannins. The methanol extract of R. coriaria was analyzed by adding 0.1 mL of previously prepared 15 mL DMSO-crude extract solution dissolved in 7.5 mL of distilled water.…”
Section: Determination Of Total Tanninsmentioning
confidence: 99%
“…Isoleucine (Ile), leucine (Leu), valine (Val) known as branched chain amino acids (BCAAs), have several physiological functions, including protein synthesis, improving insulin resistance, proliferation of lymphocyte, and reducing the apoptosis of hepatocyte. [6][7][8][9][10] Moreover, BCAAs supplements enhance aerobic exercise and decreases the rate of muscles fatigue. 11 The high BCAA plasma level in diabetic patients suggested that these acid could be involved in the development of T2DM.…”
mentioning
confidence: 99%
“…11 The high BCAA plasma level in diabetic patients suggested that these acid could be involved in the development of T2DM. 9,12 Interestingly, it was reported that BCAAs could affect the PI3K/AKT/mTOR pathway where it can enhance their pivotal role in glucose homeostasis via activating mTORC1. 13 It was suggested that BCAAs could provoke negative feedback loop by mTORC1 activation causing inhibition of PI3K/AKT/mTOR pathway, which reverses the oxidative stress © 2021 the authors.…”
mentioning
confidence: 99%